Phaseless Microwave Tomography Assessment for Breast Imaging: Preliminary Results - Sandra Costanzo; Giuseppe Lopez (International Journal of Antennas and Propagation)
In the present work, a phaseless approach for microwave imaging applications is presented. The proposed solution strategy is based on the formulation of the scattering phenomena in terms of contrast source, while no phase-recovery stage is involved into the numerical procedure, thus providing a phaseless single-step resolution method. The image recovering potentialities of the discussed method are numerically validated by successfully distinguishing different tissues of a slice breast model, with a tumor located wherein. The above preliminary assessment encourages the adoption of the proposed solution in the framework of biomedical imaging.